HUBUNGAN KONGRUENSI KARIR DENGAN ORANG TUA DAN KEMATANGAN KARIR PADA SISWA KELAS XI SMK NEGERI 7 SEMARANG - MILLA FAUZIAH CANDRA; Dian Ratna Sawitri (Faculty of Psychology, Diponegoro University, 2017)
Competition of an increasingly advanced work world there are also more qualified human resources. This makes SMK students need to increase the ability to be able to compete in the work. Therefore, it is important for students of vocational school to get career maturity. This study aims to determine the relationship between adolescent career congruence-parents with career maturity in students of class XI SMK N 7 Semarang. The hypothesis in this study there is a significant positive relationship between the perceived career congruence of adolescent-parents and career maturity. The population in this study were students of class XI SMK N 7 Semarang spread in 8 classes with the number of research samples of 275 students, using cluster random sampling technique. Data collection using Maturity Career Scale (35 valid items, α = .91) and The Adolescent-Parents Career Congruence Scale (12 valid items, α = .89) which have been tested on 138 students. Simple regression analysis showed a significant positive relationship between adolescent-parent career congruence with career maturity, with rxy value = .54 (p <.001). The higher the level of congruence of adolescents-parents, the higher the maturity of student career, and vice versa. The perceived career congruence of adolescent-parents provide effective contribution of 29% on career maturity, while 71% is owned by other factors. Further research is expected to conduct a joint search, so that can enrich the results of further research. In addition, students and parents are expected to work together in realizing career goals that match the interests, talents and abilities of students.